2020
DOI: 10.3233/jnd-200543
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Quantitative MRI and Muscle Histopathology in Muscle Biopsies from Healthy Controls and Patients with IBM, FSHD and OPMD

Abstract: Background: Muscle MRI is increasingly used as a diagnostic and research tool in muscle disorders. However, the correlation between MRI abnormalities and histopathological severity is largely unknown. Objective: To investigate correlations between muscle MRI abnormalities and histopathological severity in healthy controls and patients with muscle disease. Methods: We performed quantitative MRI and histopathological analysis in 35 patients with inclusion body myositis, facioscapulohumeral muscular dystrophy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…In addition to muscle deterioration, excessive muscle fibrosis negatively affects muscle function and is an important hallmark of FSHD [ 44 ]. We therefore additionally examined the level of fibrosis in TA and DIA muscles using immunostaining for a commonly used marker of fibrosis, collagen VI [ 45 , 46 ] ( Figure 5 b,e,g).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to muscle deterioration, excessive muscle fibrosis negatively affects muscle function and is an important hallmark of FSHD [ 44 ]. We therefore additionally examined the level of fibrosis in TA and DIA muscles using immunostaining for a commonly used marker of fibrosis, collagen VI [ 45 , 46 ] ( Figure 5 b,e,g).…”
Section: Resultsmentioning
confidence: 99%
“…This is also supported by a STIR‐T1 correspondence in the majority of muscles in the thigh and leg (Video 1 ). Evidence that STIR‐positive signal precedes the muscle degeneration has previously been reported in both acquired and genetic myopathies, such as idiopathic inflammatory myopathies and facioscapulohumeral muscular dystrophy [ 47 , 48 , 49 ] where STIR positivity corresponded to muscle edema and, more specifically, to inflammation [ 14 ]. To date, there is no evidence of an inflammatory process behind muscle degeneration in DM1 muscle biopsies.…”
Section: Discussionmentioning
confidence: 97%
“…Muscle magnetic resonance imaging (MRI) represents the gold standard technique for a muscle imaging study, providing useful information for diagnostic purposes through the detection of disease‐specific patterns of muscle involvement in various neuromuscular conditions [ 8 , 9 ]. Furthermore, muscle MRI has been considered a biomarker of disease progression [ 10 , 11 , 12 ], and also a potential non‐invasive tool to better understand the pathophysiology of specific muscle diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent 48-week Losmapimod trial in 80 FSHD subjects also found a significant improvement in fat infiltration of some affected muscles with Losmapimod compared to placebo [ 27 ]. Notably, this study also utilized MRI STIR hyperintensity as a guide for muscle biopsy, as previous investigations have found that active inflammatory cell infiltration may be present in these areas [ 110 , 117 , 118 ].…”
Section: Outcome Measures In Fshd Clinical Trialsmentioning
confidence: 99%